2015
DOI: 10.1097/mao.0000000000000759
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Dexamethasone for Noise-induced Hearing Loss

Abstract: Dexamethasone exerts reliable therapeutic effects when used to treat NIHL. It seems that the protective effects may differ by the routes of administration as the OCs were better preserved in the IP group and the ET-OHC synapses were more intact in the IT group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…A single intratympanic injection of OTO-104 ensures the presence of dexamethasone in the inner ear compartment for days to weeks [Wang et al, 2009;Piu et al, 2011], maximizing the potential of dexamethasone to provide otoprotection against trauma over time. In support of this, investigators have reported that a dexamethasone solution can attenuate hearing loss, but only when the drug is delivered continuously to the inner ear via a perfusion pump [Takemura et al, 2004] or given intratympanically on multiple occasions following trauma [Han et al, 2015]. Taken altogether, these findings indicate that the therapeutic potential of dexamethasone is best achieved when the drug remains present in the inner ear compartment for extended periods of time -therapeutic properties that are clearly afforded by OTO-104.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…A single intratympanic injection of OTO-104 ensures the presence of dexamethasone in the inner ear compartment for days to weeks [Wang et al, 2009;Piu et al, 2011], maximizing the potential of dexamethasone to provide otoprotection against trauma over time. In support of this, investigators have reported that a dexamethasone solution can attenuate hearing loss, but only when the drug is delivered continuously to the inner ear via a perfusion pump [Takemura et al, 2004] or given intratympanically on multiple occasions following trauma [Han et al, 2015]. Taken altogether, these findings indicate that the therapeutic potential of dexamethasone is best achieved when the drug remains present in the inner ear compartment for extended periods of time -therapeutic properties that are clearly afforded by OTO-104.…”
Section: Discussionmentioning
confidence: 54%
“…A recent study from Han et al [2015] compared the therapeutic effect of dexamethasone in a mouse paradigm of noise-induced hearing loss administered systemically versus intratympanically. The authors noted that both routes afforded protection against noise trauma but required multiple administration of dexamethasone (daily for 5 days for the systemic route).…”
Section: Discussionmentioning
confidence: 99%
“…Steroids, specifically intratympanic dexamethasone, may have a therapeutic beneficial effect on NIHL when given before [162] or after [163] acoustic trauma in animals. Although an effect is shown in a wide range of dosages, higher dosages appear to be associated with better hearing preservation [162].…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Our data indicate that the 6% Dex hydrogel results in faster hearing recovery with significantly smaller threshold shifts at 16 kHz 7 days after noise exposure and protects SGCs as indicated by a higher SGC density in the first turn of the cochlea 28 days after noise trauma. An otoprotective effect of intratympanic Dex application has been well described in previously published studies [Barriat et al, 2012;Han et al, 2015;Honeder et al, 2016], and there is literature supporting otoprotective effects of topically applied TAAC [Braun et al, 2011;Kiefer et al, 2007;Ye et al, 2007]. Another line of research showed that the intratympanic application of POX407 hydrogels results in sustained glucocorticoid release, which is by now also evaluated in clinical studies Lambert et al, 2012;Wang et al, 2009].…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, the efficacy of systemic glucocorticoid treatment of conditions affecting the inner ear is limited by the low blood flow to the cochlea and the blood-perilymph barrier, which result in low perilymph concentrations of the active compound [Nakashima et al, 2003;Yang et al, 2011]. To minimize side effects and achieve higher perilymph drug concentrations, administration of glucocorticoids directly to the round window membrane via intratympanic injection has been preclinically evaluated and translated into clinical practice [Bird et al, 2011;Chou et DOI: 10.1159/000487662 al., 2013; Han et al, 2015;Shea et al, 2012]. Because aqueous solutions drain rapidly through the Eustachian tube, various approaches aiming at a sustained delivery to the inner ear have been evaluated [Barriat et al, 2012;Borden et al, 2011;Plontke et al, 2009].…”
Section: Introductionmentioning
confidence: 99%